PENGARUH VARIASI TEKANAN SUCTION TERHADAP KINERJA AC MOBIL - Wardika, Wardika; Setiawan, Aa; Suwandi, Dedi; Casinih, Casinih (Politeknik Negeri Sriwijaya, Indonesia, 2022)
A refrigerant is a functioning liquid that flows in the refrigeration cycle which causes a cooling effect on the refrigeration machine. This study aims to determine the impact of refrigerant suction pressure on the performance of car air conditioners. The refrigerant pressure in the refrigeration system can increase and decrease the performance of the A/C system. The test was carried out by varying the 3 refrigerant pressures, 10psi, 20psi, and 30psi on the Car AC trainer testing tool. Based on testing and data processing, the system efficiency performance at 10psi pressure is 81.26%, at 20psi pressure is 81.27% and at 30 psi pressure is 82.13% with actual COP of 6.98, 7.24, 7.36, and Carnot COP of 8.56 respectively. , 8.92, 8.95. Then the impact of changes due to pressure variations in the system on cabin temperature is 22.52℃, 23.01℃, and 23.45℃, respectively. Changes in refrigerant pressure in the car AC engine will affect system performance, where the more significant the suction pressure is given, the efficiency, and the COP value will increase as well as the compressor work and the cabin temperature will increase.